(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This study aims at assessing the quality of sachet water sold in Gashua, Bade L.G.A. of Yobe State, Nigeria. Sachet water were obtained from five different factories, named: A, B, C, D and E. Heavy metals’ concentrations were analysed using Atomic Absorption Spectrophotometry and standard analytical procedures were used to assay for the physicochemical parameters. The results obtained from this study revealed that the concentrations of lead (0.12± 0.01, 0.12± 0.01, 0.18± 0.01, 0.05± 0.01 and 0.13± 0.01), cadmium (0.01±0.01, 0.02±0.01, 0.02±0.01, 0.03±0.01, 0.03±0.01) and arsenic (0.11±0.00, 0.14±0.01, 0.22±0.00, 0.09±0.01, 0.13±0.01) for samples A, B, C, D and E were significantly higher than the WHO permissible values of 0.02+0.00, 0.003+0.00 and 0.01±0.00 respectively. Zinc was not detected in any of the samples but iron was detected at significantly lower value of 0.002±0.00, 0.03±0.01, 0.05±0.01, 0.03±0.00 and 0.03±0.00 for samples of A, B, C, D and E respectively, when compared with the WHO standard value of 3.00±0.00. Chromium showed higher concentration in samples A, C and E but samples B and C fall within the WHO permissible limit of 0.05±0.00. Conductivity, TDS and sulphate for samples A, B, C, D and E were seen to be significantly lower than the WHO standard value. Turbidity and total suspended solids were found to be above the WHO limit. In conclusion, the results of this study have shown that some metals of the various branded sachet water do not meet the recommended standard due to high concentration of heavy metals and physicochemical parameters beyond...